Coping Stress in Islamic Perspective - Abidah Ayu; Suhendar (Proceeding International Conference on Religion, Science and Education, 2023)
In everyday life, humans cannot be separated from stressful conditions. Therefore, humans need to have stress coping skills and cognitive training to stay in a sane condition. Stress coping is a process that individuals go through in resolving or managing circumstances that cause stress in response to situations that threaten them both physically and psychologically. This topic has great attention in the study of Psychology. Furthermore, this paper aims to examine stress and stress coping in an Islamic perspective whose sources will be taken from the Qur'an and Hadith as an effort to obtain a better life. This paper also seeks to bring harmony between psychological concepts and Islamic concepts to become a meeting point in studying stress coping. In Islam, coping with stress is through sincerity, patience, remembrance, repentance, prayer, positive thinking and optimism. In line with the concepts in Islam, in psychology, coping stress strategies include self-activity, strategic planning, self-control, seeking social support, acceptance, and religiosity.